Nursing students’ experiences and perceptions regarding in-class flipped classroom: a mixed-methods study - Dongmei Zhang; Anle Huang; Yunxiao Lei; Haiyang Liu; Liu Yang; Congzhi Wang; Ting Yuan; Xiaoping Li; Lin Zhang; Wenyuan Shang (BMC Medical Education)
Abstract Background In medical education, flipped classroom, providing innovative ideas for teaching reform, has been actively promoted. However, it requires completing preparatory work before the classroom, with workload burden, time constraints, and lack of familiarity being the most common challenges associated with the pre-class activity. Moreover, pre-class activities inevitably impose multiple burdens and challenges on nursing students, potentially leading to fatigue and hindering their ability to cope effectively, thus impeding the achievement of the intended learning outcomes. Implementing an in-class flipped classroom approach could help alleviate these challenges. This study aimed to deepen understanding of nursing students’ experiences and perceptions in the in-class flipped classroom settings, offering valuable insights for the reforming of nursing professional courses. Methods This study employed a mixed-methods study. The quantitative phase collected 107 nursing students’ learning satisfaction with the in-class flipped classroom via questionnaires. The data were analyzed employing SPSS 25.0. In the qualitative phase, semi-structured interviews incorporating four focus group discussions were conducted with 57 nursing students. The Colaizzi seven-step analysis method was employed to analyze the interview data. Results The quantitative results showed that the top three ratings contributing to learning satisfaction in the in-class flipped classroom were mastering knowledge effectively, creating a good classroom atmosphere, and improving communication and collaboration skills. The median score for all items was no less than 4/5. The qualitative results revealed five themes: progressive learning experience, teaching efficiency and effectiveness, developing abilities, impact on academic and occupational emotions, and needing to be improved. Finally, the integrated results validated the accuracy and rationality of the data. Conclusion The in-class flipped classroom, an innovative teaching strategy, enhanced teaching effectiveness and efficiency. This approach is well-suited for the reform of teaching methods in nursing practice courses.